Aortic Arch Calcification and the Risk of Cancer: A Population-Based Cohort Study - van der Toorn, Janine E.; van der Willik, Kimberly D.; Ruiter, Rikje; Vernooij, Meike W.; Stricker, Bruno H.Ch.; Schagen, Sanne B.; Ikram, M. Arfan; Kavousi, Maryam; Bos, Daniel (Frontiers in Oncology, 2020)
Background: Atherosclerosis and cancer share multiple disease pathways. Yet, it is unclear if atherosclerosis is associated with a subsequent higher cancer risk. We determined the association of atherosclerotic calcification in the aortic arch, as proxy for systemic atherosclerosis, with the risk of cancer. Methods: Between 2003 and 2006, 2,404 participants (mean age: 69.5 years, 52.4% women) from the prospective population-based Rotterdam Study underwent computed tomography to quantify calcification in the aortic arch. Participants were followed for the onset of cancer, death, loss to follow-up, or January 1st, 2015, whichever came first. We computed sex-specific tertiles of aortic arch calcification volumes. Next, we examined the association between the volume and severity (i.e., tertiles) of aortic arch calcification and the risk of cancer using Cox proportional hazard models. Results: During a median (interquartile range) follow-up of 9.6 years (8.9-10.5), 348 participants were diagnosed with cancer. Participants with the greatest severity of aortic arch calcification had a higher risk of cancer (hazard ratio for the third tertile compared to the first tertile of aortic arch calcification volume in the total population is 1.39 [95%CI=1.04-1.86]). Conclusions: Individuals with the most severe amount of aortic arch calcification had a higher risk of cancer. While this could reflect the impact of long-term exposure to shared risk factors, it might also point towards the co-occurrence of both conditions.